Implementation of E-Learning Based on Mic.Teams In Science Learning In Elementary School - Ernawanto, Yoni; Desstya, Anatri; Hidayati, Yulia Maftuhah (Universitas Muhammadiyah Surakarta, 2021)
Purpose: This study aims to describe 1) Mic.Teams e-learning planning on science online learning in Elementary School 2) implementation of Mic. Teams -based e-learning 3) Mic.Teams based e-learning evaluation. Methodology: This research approach is qualitative, with descriptive method. Data were collected by interview and observation. Interactive data analysis techniques are data reduction, data presentation, and drawing conclusions. While the validity of the data with triangulation techniques and sources. Data sources consist of principals and teachers. Results: The results showed that 1) Mic.Teams e-learning planning on science online learning at SDN 1 Wonogiri are carried out systematically by the school and teachers, namely the school principal’s policy of forming an IT E-Learning teams, register teachers and students in office 365 accounts and teachers prepare distance learning tools in the form of syllabus, prota, promissory notes, lesson plans, teaching materials, assessment programs and LKPD. 2) Implementation of Mic.Teams -based e-learning begins with the teacher creating a virtual class and including members in the created class and utilizing the online meeting features, posts and assignments in learning 3) Mic.Teams based e-learning evaluation are conducted every month covering the cognitive, affective and psychomotor domains. The results of this study are used as a source of input and reflection material for schools about the implementation of Mic.Teams and as material for self-evaluation to contribute to efforts to improve the quality, process and learning outcomes of students online.